Erect Position as the Alternative Technique in Achilles Tendon US: Comparison with Prone Position - Lailatul Muqmiroh; Safinah Fajarini Yusfadhiyah; Paulus Rahardjo (Program Pendidikan Vokasi Universitas Indonesia, 2018)
Background : Ultrasonography (US) is the cheaper and non invasive modality to determine Achilles tendon. Prone position is the standart position of Achilles tendon US. However, it is a discomfort for an uncooperative patient and a difficult technique too. The erect position is an alternative technique of Achilles tendon US. The goal of this study is to compare the erection as an alternative position with prone as a standart position.Material and Methode: The patient who had an injury or any inflamation process of Achilles tendon were excluded. The patient underwent two positions of Achilles tendon US, 900 and dorsoflexi. Longitudinal axis measured tendon thickness and a transversal axis which covered a cross-sectional area of the tendon.Result: From all the 21 patients coming, 13 patients were males (61,9%), and eight patients were females (38,1%). The mean of tendon thickness and cross-sectional area in 900 prone positions were 4,24±0,24 mm, 30,08±2,86 mm, respectively. The mean of tendon thickness and cross-sectional area in 900 erect positions were 4,27±0,23 mm, 31,36±2,19 mm, respectively. There was no anisotropy effect during longitudinal axis examination. Conclusion: We found that there were no significant differences between a prone and erect position (p<0.05). The erect postion could be an alternative position, uncooperative patient in particular, without reducing the diagnostic value. Keywords: Achilles tendon the US, erect position, prone position, tendon thickness, cross-sectional area